Advances in Micro- and Nanomechanics - Eremeyev, Victor A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book focuses on recent advances in both theoretical and experimental studies of material behaviour at the micro- and nano-scales. Special attention is given to experimental studies of nanofilms, nanoparticles and nanocomposites as well as tooth defects. Various experimental techniques were used. Magneto- and thermoelastic coupling were considered, as were nonlocal models of thin structures.